Central nervous system tumors: a histopathological study - Jat, Kailash Chand; Vyas, S. P.; Bihari, Naseem A.; Mehra, Kuldeep (International Journal of Research in Medical Sciences, 2016)
Background: Brain tumors can originate in almost any type of tissue, cell or mixture of cell types in the brain or spinal cord. Tumors in different areas of the central nervous system may be treated differently and have a different prognosis. Methods: In the period between 2011-2015, we studied on 59 patients diagnosed with CNS tumors according to the World Health Organization’s diagnostic criteria. Patient data were retrieved from the archives of the department of Pathology, Sardar Patel Medical College, Bikaner. The diagnosis in all the cases were made on hematoxylin & eosin stained slides of processed tissue. Results: Patients ages ranged from 3.5-65 years with a mean age of 41.2 years and a male to female ratio of 1.8:1. Majority of tumors had intracranial location (55 cases, 93.23%). 91.5% tumors were solid in consistency. Frontal lobe (37.3%) was the predominant affected region. Most tumors were originated from neuroepithelium (67.8%) followed by meninges (22.03%). When examining the data pertaining to specific types of tumors, most frequent type of CNS tumors was astrocytoma (31 cases, 52.5%), followed by meningioma (13 cases, 22%). Conclusion: The most frequent type of CNS tumours in this study was astrocytoma, followed by meningioma. Males are at much higher risk of developing CNS tumour in comparison to females (1.8:1). WHO Grade IV lesions were more common in our institutional set up. The exact histological diagnosis of CNS tumors is essential to predict the prognostic factors.